Genetic variability of Indonesian landraces of Vigna subterranea: Morphological characteristics and molecular analysis using SSR markers - MUHAMMAD FAUZAN FARID AL HAMDI; Asep Setiawan; Satriyas Ilyas; Wai Kuan Ho (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Alhamdi MFF, Setiawan A, Ilyas S, Ho WK. 2020. Genetic variability of Indonesian landraces of Vigna subterranea: The morphological characteristics and molecular analysis using SSR markers. Biodiversitas 21: 3929-3937. Bambara groundnut (Vigna subterranea (L.) Verdc.) is a potential grain, which can be considered as an alternative source of protein and carbohydrate. Due to unavailability of commercial bambara groundut cultivar in Indonesia, the characterization of bambara groundnut landraces is an important step before developing cultivar with traits of interest. The objective of the research was to access genetic variability of Indonesian landraces of bambara groundnut with different seed coat colors based on morphological and molecular markers. The experiment was arranged as split-plot in a complete randomized block design with the main plot was cultivation methods and the sub plot was landraces. There were differences in leaf shape and pod shape among the landraces. There were two main clusters of Indonesian landraces of bambara groundnut with 88.28% similarity. The first cluster was Cream, Brown Sumedang, Black Sumedang and Black Tasikmalaya, and the second cluster was Black Sukabumi, Brown Gresik, Black Madura, and Black Gresik. The result based on SSR marker with capillary electrophoresis indicated Black Gresik and Black Madura landraces were different from other Indonesian landraces.  Cream Sumedang or Brown Sumedang from the first cluster and Black Gresik or Brown Gresik from the second cluster have the farthest distances for developing improved variety of bambara groundnut.